Educación emocional y su relación con la autoestima de las estudiantes de la Carrera de Educación Inicial de la Universidad Nacional de Chimborazo. - Salazar Almeida, Pilar Aide (2024)
Emotional education and its relationship with the self-esteem of the students of the Initial Education career of the National University of Chimborazo, is a topic of great importance since it influences the improvement of interpersonal and intrapersonal relationships, between the students and their environment. , because on many occasions teachers, especially at the higher level, do not usually pay due attention to it, then several questions arise: How important is emotional education for improving self-esteem? Should emotional intelligence be considered as a transversal axis in the formation of people's capabilities? How does emotional education play an important role in the development of students in the Initial Education career? For this reason, the purpose of this research is to propose a manual of strategies that promote emotional education through various work strategies applicable in the classroom that help strengthen the self-esteem of students in the Initial Education career. The object of study in this project are 42 students from the Initial Education program at the National University of Chimborazo. For data collection, only a previously designed survey was used. The results obtained demonstrate that students have an unsatisfactory level of emotional development, which gives rise to the need to implement strategies that mitigate this problem.